Raman spectroscopy of graphite intercalation compounds: Charge transfer, strain, and electron-phonon coupling in graphene layers - Chacón-Torres, Julio C.; Wirtz, Ludger; Pichler, Thomas (Physica Status Solidi. B: Basic Solid State Physics, 2014)
Graphite intercalation compounds (GICs) are an interesting and highly studied field since 1970’s. It has gained renewed interest since the discovery of superconductivity at high temperature for CaC6 and the rise of graphene. Intercalation is a technique used to introduce atoms or molecules into the structure of a host material. Intercalation of alkali metals in graphite has shown to be a controllable procedure recently used as a scalable technique for bulk production of graphene, and nano‐ribbons by induced exfoliation of graphite. It also creates supra‐molecular interactions between the host and the intercalant, inducing changes in the electronic, mechanical, and physical properties of the host. GICs are the mother system of intercalation also employed in fullerenes, carbon nanotubes, graphene, and carbon‐composites. We will show how a combination of Raman and ab−initio calculations of the density and the electronic band structure in GICs can serve as a tool to elucidate the electronic structure, electron–phonon coupling, charge transfer, and lattice parameters of GICs and the graphene layers within. This knowledge of GICs is of high importance to understand superconductivity and to set the basis for applications with GICs, graphene and other nano‐carbon based materials like nanocomposites in batteries and nanoelectronic devices. Raman spectroscopy of graphite intercalation compounds (GIC) has become a powerful tool in the study of graphene under the effects of charge transfer and strain. The Raman response observed in GICs has been assigned to specific graphene layered environments present in the compound, whereas the G‐line in stages I and II (golden and blue graphite) has revealed important implications in the electron‐phonon coupling constant responsible for superconductivity.